Differential impacts of 2016 coral bleaching on coral reef benthic communities at Sekotong Bay, Lombok Barat, Indonesia - IMAM BACHTIAR; TRI ARYONO HADI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Bachtiar I, Hadi TA. 2019. Differential impacts of 2016 coral bleaching on coral reef benthic communities at Sekotong Bay, Lombok Barat, Indonesia. Biodiversitas 20: 570-575. Coral bleaching has been a major causal factor of coral mortality worldwide in the last two decades and it is therefore threaten food security. Understanding post-bleaching recovery is therefore very crucial to formulate strategy in promoting natural coral reef recovery. The present study documented coral reef communities both in pre- and post-bleaching event in early 2016. The results show that coral bleaching variably reduced coral and soft-coral covers. Sponge and other fauna cover considerably fluctuated. Since the individual number of soft-coral, sponge and other fauna were small, there is likely no big impact of coral bleaching. Among 12 study sites, 11 sites showed significant reduction of coral cover but one site showed only little fluctuation. Overall mean reduction of coral cover was about 18%. Consequently, algal cover increased by about 24%. The present study revealed differential coral bleaching impact between outer- and inner- reefs. At outer reefs, coral community suffered more severe mass coral mortality than those at inner reefs. This disparity is likely owing to initial coral cover and species composition of the coral communities. In the second year, there is still no visible coral recruitment from larvae. Cascade effects of land-clearing and overfishing due to increasing tourism development is very likely to be additional major stress that pause post-bleaching coral reef recovery at Sekotong Bay, Lombok Island, Indonesia.